(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
muscle and its impact on the requirements of performance and effectiveness, so the teachers’ ideas tended toward the process of enhancing the level, as it became a concern for all those involved in the field of training in all their specialties and that access to the sports championship or maintaining the level. The study included an introduction and the significance of research in the use of measurements of cardiac muscle and its impact on the requirements of performance and effectiveness, so the teachers’ ideas tended toward the process of enhancing the level, as it became a concern for all those involved in the field of training in all their specialties and that access to the sports championship or maintaining the level. In addition, these results can be relied upon as a result of the advancement of scientific research and as a means of resolving issues associated with determining or halting the athletic level; hence, the significance of research involving the use of modern technical instruments to examine the heart muscle and its measurements. The problem of the research was used a form of a question: Do the measurements of the cardiac muscle have correlations with the skill performance requirements of volleyball? As for the research objectives, it was to know the effect of some cardiac muscle measurements for young volleyball players and to identify the skill performance requirements of young volleyball players, as well as to know the relationship between the cardiac muscle measurements under study and the skill performance requirements of young volleyball players. As for the research’s hypotheses, they involve the existence of a statistically significant association between cardiac measures and the needs of volleyball skill performance. As for the research’s hypotheses, they involve the existence of a statistically significant association between cardiac measures and the needs of volleyball skill performance. The most important conclusions reached by the researcher are the improvement of the functional level of the sample and the development of measurements of the cardiac muscle in the sample. Regarding the recommendations, the most essential ones were the necessity of validating the planned training objectives during tests and measurements, as well as the value of functional and cardiac measurements.